Advanced topics in forensic DNA typing methodology - Butler, John M. (John Marshall) 1969- (Elsevier Academic Press, 2015)
This book provides the most detailed information written to-date on DNA databases, low-level DNA, validation, and numerous other topics including a new chapter on legal aspects of DNA testing to prepare scientists for expert witness testimony